La rigenerazione secondo il PNRR. Etnografia dei documenti e delle pratiche di una proposta progettuale sul Piano nazionale borghi in Umbria - Petrangeli, Enrico (Antropologia Pubblica, 2024)
The paper takes its cue from Wittgenstein’s suggestion to look for the meaning of words in the concrete use made of them in particular “language games” and “situational contexts”. The language game in question is Regeneration, both cultural and social, which, in almost all its bureaucratic declinations, is however always based on urban regeneration and/or territorial development. Ethnography and hermeneutics are applied to documents produced by the Italian “National Plan Borghi PNRR-MIC” and by the Third Sector and Social Economy Section of the Umbria Region. The “situational context” is the design team of which the author was a member and that gave opportunities for participant observation. The bureaucratic shaping of the concept of Regeneration is read from a perspective of militant and reflexive ethnography, as a critique of the rhetorics and practices of territorial development.